O ESPAÇO E A CONSTITUIÇÃO DO SUJEITO MELANCÓLICO: UM ESTUDO DE BARBA ENSOPADA DE SANGUE E OUTRAS OBRAS DE DANIEL GALERA - SAMARA PEREIRA SOUZA DE LIMA (2024)
This thesis aims to analyze the confluence and implications between the fictional space element and melancholy, in order to verify the configuration of the melancholic subject in the contemporary Brazilian novel Barba ensopada de sangue (2022), and in other works by Daniel Galera. During the research, the concepts of melancholy and its possibilities of manifestation were observed through the studies of researchers such as Sigmund Freud (2011), Luiz Costa Lima (2017), Moacyr Scliar (2003), Hélder Moura (2022), and Jean Starobinski (2016), among others. Regarding the fictional space, the concepts of scholars Gaston Bachelard (1978), Ricardo Gullón (1980), and Osman Lins (1976) were presented. The thesis sought to analyze how space contributes to provoking and revealing the melancholic nuances that make up the formation of the protagonist of Barba ensopada de sangue (2022). The implications between space and melancholy, and the constitution of the melancholic subject, were also analyzed in other characters by the author, in the works Até o dia em que o cão morrer (2007), Mãos de cavalo (2010), Cordilheira (2008), Meia-noite e vinte (2016) and O deus das avencas (2021). In the meantime, in Barba ensopada de sangue (2022), issues such as the composition of the hostile space, the city in which the plot unfolds, and the other symbolic manifestations of this articulating element of the narrative were essential to highlight melancholic aspects such as the family crisis, loneliness, the feeling of not belonging, rejection, isolation, unpretentiousness, and the existential emptiness of the protagonist represented. Furthermore, through this study, it is possible to affirm that the melancholic nuance is a constant in the representation of the characters analyzed, which indicates an aesthetic aspect of Daniel Galera's production. Thus, this thesis proves to be significant for the contributions it leverages regarding the consonance between space and melancholy in the constitution of the author's characters, especially the protagonist of Barba ensopada de sangue (2022).